Empirical Evidence on the Effectiveness of Social Public Procurement Policy: The Case of the Swiss Apprenticeship Training System - Mirjam Strupler Leiser; Stefan C. Wolter (Institute for the Study of Labor (IZA), 2016)
In this paper we assess the effectiveness of a social public procurement policy in Switzerland that gives firms that train apprentices a preferential treatment. We estimate the effectiveness of this social procurement policy on a firm's training participation, training intensity, and training quality using information from a representative and large firm survey. The results show that the policy increases the number of training firms, and does not affect training quality negatively. However, the effect is limited in size, as only small firms and firms operating in sectors where public procurement represents a large share of the business, are affected positively.
Keywords: H32; I28; J08; 330; apprenticeship training; difference-in-differences; matching; public procurement policy; social public procurement